PERBANDINGAN KADAR PROTHROMBINE TIME DAN ACTIVATED PARTIAL THROMBOPLASTINE TIME PADA PASIEN DM TIPE 2 KAKI DIABETIK DENGAN TANPA KAKI DIABETIK DI RSUP DR. M. DJAMIL PADANG TAHUN 2019 - Decroli, Rezeki Penta; Yulia, Dwi; Miro, Saptino (Lembaga Pendidikan dan Penelitian Manggala Institute, 2025)
Diabetic Foot Ulcers are one of the most common, serious, and costly complications of type 2 diabetes mellitus. Diabetic Foot Ulcers have become more common in tandem with the rising prevalence of type 2 diabetes mellitus. Changes in many hematological parameters, such as Prothrombine Time and Activated Partial Thromboplastine Time, are influenced by the mechanism of diabetic ulcer occurrence. Understanding the various aspects of hematological parameters will help in the prevention and treatment of diabetic foot ulcers. This study aims to determine the comparison in the hematological profile in type 2 DM patients with and without diabetic foot ulcers at Dr. M. Djamil Padang hospital in 2019. This type of research is an observational analytic study with a retrospective design using medical record data of patients at Dr. M. Jamil Padang hospital from August 2020 to March 2021. The sample consisted of the medical records of patients with type 2 diabetes mellitus with foot ulcers and without foot ulcers, respectively, as many as 60 subjects. Bivariate analysis using independent t-test or Mann Whitney test. The results showed that the mean PT level of type 2 DM patients with diabetic foot ulcers was 12.8417 ± 2.36939, without diabetic foot ulcers 11.997 ± 1.8325 (p <0.001). The mean aPTT of patients with diabetic foot ulcers was 41.2733 ± 35.1686, without diabetic foot ulcers 32.912 ± 13.1263 (p <0.001). This study concludes that there are significant in between type 2 DM patient with foot ulcer and without foot ulcers.